Posthypertonic Lysis of Red Blood Cells in Combinated Media - Chabanenko, Olena O.; Orlova, Natalia V.; Shpakova, Natalia M. (Problems of Cryobiology and Cryomedicine, 2019)
Probl Cryobiol Cryomed 2019; 29(2): 154